Serviço Social em dois tempos: a experiência como destinatário do trabalho do assistente social e sua ressignificação quando profissional da área - Lima, Neusa Cavalcante (2018)
This dissertation contributes to the production of knowledge to Social Work. It addresses the social meaning extracted from the narrative of social workers who, before the academic formation, lived the experience of having been attended in a program or a project, in which their profession was inserted. Specific objectives were determined: to analyze the Social Work practice by the meaning attributed to the experiences lived as users or recipients of the professional activity; to identify in the narratives how their profession is expressed and what mediations were mobilized by the professionals in the work accomplished and how the meaning of lived experience guides the professional activity and returns to the construction of new meanings for the profession. The framework adopted for this work found support in historical materialism, in the history philosophy, concept proposed by Walter Benjamin and in the experience approaching by Edward P. Thompson. The research revealed the thomposian approach, present in the theoretical fundaments in Social Work from the end of the 1980s, and that gained visibility after the publication of "Subaltern classes and social assistance" by Yazbek in 1993. The oral history methodology was adopted and found support in Alessandro Portelli, Yara Aun Khoury and in Maria Lúcia Martinelli’s professional activity concerning Social work. The methodological option was based on oral history and, according to the density of the narratives, revealed similarities with the history of life. In the interviews, the emerged categories of analysis were domestic violence against women and the institutional reception, linked to the specific contexts of care in Social Work. In the analysis of the narratives, the professional culture emerged as part of their world experience and as new possibilities of sociability